Association Between Metabolic and Hormonal Derangements and Professional Exposure to Urban Pollution in a High Intensity Traffic Area - Molfino, Alessio; Amabile, Maria Ida; Muscaritoli, Maurizio; Germano, Annunziata; Alfano, Rossella; Ramaccini, Cesarina; Spagnoli, Alessandra; Cavaliere, Liberato; Marseglia, Gianluca; Nardone, Antonio; Muto, Giuseppina; Carbone, Umberto; et al. (Frontiers in Endocrinology, 2020)
Rationale: Studies suggest a relation between exposure to air particulate matter (PM)2.5 pollution and greater cardiovascular morbidity, as well as increased risk for obesity and diabetes. We aimed to identify association(s) between nutritional and metabolic status and exposure to environmental pollution in a cohort of policemen exposed to high levels of air-pollution. Methods: We considered adult municipal policemen, working in an urban area at high-traffic density with documented high levels of air PM2.5 (Exposed-group) compared to Non-exposed policemen. Clinical characteristics, including the presence/absence of metabolic-syndrome, were recorded and serum biomarkers, including adiponectin, leptin and ghrelin, were assessed. Results: 199 participants were enrolled, 100 in the Exposed-group and 99 in the Non-exposed group. Metabolic-syndrome was documented in 32% of Exposed-group and in 52.5% of Non-exposed group (P=0.008). In the Exposed-group, we found a positive correlation between BMI and serum leptin as well as in the Non-exposed group (P<0.0001). Within the Exposed-group, subjects with metabolic-syndrome showed lower serum adiponectin (P<0.0001) and higher leptin (P=0.002) levels with respect to those without metabolic-syndrome, whereas in the Non-exposed group subjects with metabolic-syndrome showed only higher leptin levels when compared to those without metabolic-syndrome (P=0.01). Among the participants with metabolic-syndrome, we found lower adiponectin levels in those of the Exposed-group with respect to the Non-exposed ones (P=0.007). When comparing the Exposed- and Non-exposed groups, after stratifying participants for HOMA-IR>2.5, we found lower adiponectin levels in those of the Exposed-group with respect to the Non-exposed ones (P=0.038). Conclusions: Exposure to air PM pollution was associated with lower levels of adiponectin in adult males with metabolic syndrome.